Podział cyfrowy wśród gospodarstw domowych w Polsce - Burawski, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
In the article the author deals with two problems. The first one concerns span of digital divide in Poland, including differences in the Internet availability and usage in households. The second one concerns the reasons for emergence of the discussed occurrence. Base for the discussion is digital divide analysis in Poland according to specifi c social and demographical characteristics, including comparison with the EU countries.
Keywords: gospodarstwa domowe; Polska; podział cyfrowy